PERAN ORANG TUA MENURUT ULANGAN 6:6-7 DALAM PERTUMBUHAN SPIRITUALITAS GENERASI ALPHA DI ERA DIGITAL - Sinjo Bantaeng, Rachmat Tony; Tambun, Marlin; Kase, Emanuel (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Advancement in digital era technology, particularly in social media and Artificial Intelligence, have made it significantly easier for Generation Alpha to consume various information especially through short clips. However, these advancements heightened the vulnerability to misinformation. Social media and Artificial Intelligence algorithms often amplify of such causing inaccurate information short clips to appear repeatedly on their device screen. Furthermore, the reliance on these technologies has made Generation Alpha highly addictive to social media contents and AI, often leading Gen A indifference toward matters related to spirituality. The method used in this qualitative research is a literature study and hermeneutics with an expository approach to Deuteronomy 6:6-7. The aim is to examine the relationship of Deuteronomy 6:6-7 expository and the role of parents in nurturing the spiritual growth of Generation Alpha. The study shows that God's Word must be taught repeatedly, every time and anywhere possible. Word of God must be carried out faithfully and in obedience. Based on the exposition of Deuteronomy 6:6-7, the role of parents can be understood in three dimensions: as teachers who teach, as disciplinarians who guide, and as role models to their children. Together, these responsibilities play a vital role in shaping the spiritual formation of Generation Alpha.